A synergistic use of microalgae and macroalgae for heavy metal bioremediation and bioenergy production through hydrothermal liquefaction. Issue 1 (4th December 2018) - Piccini, Marco; Raikova, Sofia; Allen, Michael J.; Chuck, Christopher J.
Abstract : In this investigation a novel synergistic approach for the bioremediation of metal-contaminated water and bioenergy production was developed. Abstract : In this investigation a novel synergistic approach for the bioremediation of metal-contaminated water and bioenergy production was developed. Two microalgae, Chlorella vulgaris and Arthrospira platensis (Spirulina), and two macroalgae, Ulva lactuca and Sargassum muticum, were used as passive bioremediation agents for the metals Ni(ii ), Zn(ii ), Cd(ii ) and Cu(ii ). The metals were added singularly and in combination between 10–150 mM. The metal contaminated biomass was then processed through hydrothermal liquefaction to yield four phases: a bio-crude oil, an aqueous phase, solid residue and gas. Both C. vulgaris and A. platensis gave high bio-crude yields of 39 and 31 wt% respectively, while U. lactuca and S. muticum gave 14% and 9% respectively. Initial studies demonstrated that the addition of up to 150 mM of the target metal sulfates to the biomass feedstock did not significantly affect bio-crude production, and, for microalgae, over 99% of the target metals were partitioned to the solid phase products predominantly as phosphates or oxides. Subsequently, bioremediation of waste water and HTL were successfully coupled, with over 80% of a 10 mM solution of the metals biosorbed, though efficacy depended heavily on the algal species. Upon HTL of the remediating biomass, the yield and composition of the bio-crude were not changed significantly. For the microalgae, the aqueous phase contained significant nitrogen, potassium and phosphate levels, and the majority of the target metals deposited in the solid phase, with over 99.5% metal recovery for Spirulina when all four metals were used. The macroalgal species were not as effective in this process, with limited phosphate recovery in the aqueous phase (albeit with extensive potassium recovery) and with less than 50% of the target metals depositing in the solid residue for the Ulva species examined, presumably due to the affinity of the metals to proteinous species rather than polysaccharide in this species. Combining microalgal bioremediation with hydrothermal liquefaction is therefore a potentially highly effective method of remediating contaminated waste waters, whilst a macroalgae based process may offer a cheaper alternative, albeit with substantially reduced efficacy. The recovery of the target metals and multiple product formation improves the economic viability of the process, thereby valorising the bioremediation process and subsidising environmental clean-up.